Biological and predictive role of ERCC1 polymorphisms in cancer. (March 2017) - Formica, V.; Doldo, E.; Antonetti, F.R.; Nardecchia, A.; Ferroni, P.; Riondino, S.; Morelli, C.; Arkenau, H.T.; Guadagni, F.; Orlandi, A.; Roselli, M.
Highlights: A review of the literature on the effect of ERCC1 polymorphisms on oxaliplatin efficacy and safety is proposed. Available evidence does not support ERCC1 genotyping to predict efficacy outcome in oxaliplatin-treated patients. ERCC1 minor alleles of rs3212986 and rs11615 polymorphisms may be associated with increased oxaliplatin toxicity. Abstract: Excision repair cross-complementation group 1 (ERCC1) is a key component in DNA repair mechanisms and may influence the tumor DNA-targeting effect of the chemotherapeutic agent oxaliplatin. Germline ERCC1 polymorphisms may alter the protein expression and published data on their predictive and prognostic value have so far been contradictory. In the present article we review available evidence on the clinical role and utility of ERCC1 polymorphisms and, in the absence of a 'perfect' trial, what we call the 'sliding doors' trial, we present the data of ERCC1 genotyping in our local patient population. We found a useful predictive value for oxaliplatin-induced risk of anemia.